Rapidly Neutralizable and Highly Anticoagulant Thrombin-Binding DNA Aptamer Discovered by MACE SELEX - Koji Wakui; Toru Yoshitomi; Akane Yamaguchi; Maho Tsuchida; Shingo Saito; Masami Shibukawa; Hitoshi Furusho; Keitaro Yoshimoto (Elsevier, 2019)
We present a rapidly neutralizable and highly anticoagulant thrombin-binding aptamer with a short toehold sequence, originally discovered by systematic evolution of ligands by exponential enrichment (SELEX) with microbead-assisted capillary electrophoresis (MACE). MACE is a novel CE-partitioning method for SELEX and able to separate aptamers from a library of unbound nucleic acids, where the aptamer and target complexes can be detected reliably and partitioned with high purity even in the first selection cycle. Three selection rounds of MACE-SELEX discovered several TBAs with a nanomolar affinity (Kd = 4.5-8.2 nM) that surpasses previously reported TBAs such as HD1, HD22, and NU172 (Kd = 118, 13, and 12 nM, respectively). One of the obtained aptamers, M08, showed a 10- to 20-fold longer prolonged clotting time than other anticoagulant TBAs, such as HD1, NU172, RE31, and RA36. Analyses of the aptamer and thrombin complexes using both bare and coated capillaries suggested that a large number of efficient aptamers are missed in conventional CE-SELEX because of increased interaction between the complex and the capillary. In addition, the toehold-mediated rapid antidote was designed for safe administration. The efficient aptamer and antidote system developed in the present study could serve as a new candidate for anticoagulant therapy. Keywords: aptamer, anticoagulant, thrombin, SELEX, antidote, toehold-mediated strand displacement, capillary electrophoresis